Raman spectra of gas mixtures in fluid inclusions: Effect of quartz birefringence on composition measurement. (17th May 2019) - Caumon, Marie‐Camille; Tarantola, Alexandre; Wang, Wenjing
Abstract: The molar composition of gas mixtures in fluid inclusions is one of the most important properties to reconstruct the Pressure, molar Volume, Temperature Composition properties of geofluids. Raman spectroscopy is a powerful tool for quantitative analysis of the composition of fluids trapped in inclusions as the peak area of each species is directly linked to concentration by its Raman scattering cross section. Previous studies proved the effect of host mineral birefringence on the shape of the stretching vibration band of liquid water, and hence on the quantitative determination of salinity, but the influence on gas‐mixture inclusions was never evaluated. In this study, the Raman signals of coexisting CO2, CH4, and N2 in two natural fluid inclusions in quartz were collected with sample rotation on the microscope stage. Peak area ratios (CO2 + /CH4, CO2 + /N2, and N2 /CH4 ) showed sinusoidal variations with a period of 45°. On the contrary, the area ratio of the two peaks of CO2 (CO2 + /CO2 − ) and the Fermi diad splitting remained constant with sample rotation. This effect is most probably due to a combination of polarization effects as previously observed for liquid water: depolarization ratios of each gas species, birefringence of the host mineral, and polarization response curve of the spectrometer. It can be canceled by placing the sample at crystal extinction position. Abstract : The molar composition of gas mixtures in fluid inclusions is one of the most important properties to reconstruct the chemical and physical properties of geofluids. Raman spectroscopy is widely used to determine composition and density of gas phase in fluid inclusions. It is demonstrated here that the birefringence of the host mineral affects these measurements, probably because of polarization effects (depolarization ratios of each gas species, birefringence of the host mineral, and polarization response curve of the spectrometer).